Surface Physics : Fundamentals and Methods - Fauster, Thomas; Hammer, Lutz; Heinz, Klaus; Schneider, M. Alexander (De Gruyter Textbook, 2020)
This work introduces concisely into modern and experimental Surface Physics. Based on many years of teaching experience, the authors present surface-specific properties and complex processes in a plain and descriptive way. Ideal for exam preparation through tasks and comprehension questions.